Long-term prognostic role of cerebrovascular disease and peripheral arterial disease across the spectrum of acute coronary syndromes. (February 2016) - Vagnarelli, Fabio; Corsini, Anna; Lorenzini, Massimiliano; Ortolani, Paolo; Norscini, Giulia; Cinti, Laura; Semprini, Franco; Nanni, Samuele; Taglieri, Nevio; Soflai Sohee, Sophia; Melandri, Giovanni; Letizia Bacchi Reggiani, Maria; et al.
Abstract: Background: In acute coronary syndromes (ACS), the influence of cerebro-vascular disease (CVD) and/or peripheral artery disease (PAD) on short-midterm outcome has been well established. Data on long-term outcome however, are limited. Our study aimed to explore the effect of CVD and PAD on long-term outcome in a cohort of unselected ACS patients, including ST-elevation (STE-ACS) and non-ST-elevation (NSTE-ACS). Methods and results: The population consisted of 2046 consecutive patients with a confirmed final diagnosis of ACS; 896 (44%) had STE-ACS and 1150 (66%) NSTE-ACS. CVD alone was present in 98 patients (5%), 282 (14%) had PAD alone, and 30 (1.5%) had both. All cause mortality at 5 years was lowest in patients without CVD/PAD (33%), intermediate in patients with either CVD or PAD (62% and 63%, respectively) reaching 80% in those with both CVD and PAD. These findings were confirmed in the STE-ACS and NSTE-ACS subgroups. CVD and PAD remained independent predictors of mortality after multivariable analysis, the combined presence of both carrying the highest risk within each ACS type (HR 4.15, 95% CI 1.83–9.44 for STE-ACS; HR 2.14, 1.29–3.54 for NSTE-ACS). Patients with CVD and/or PAD were less likely to be treated invasively and received less evidence-based treatment at discharge. Conclusions: Across the spectrum of ACS, extracardiac vascular disease harbors a negative long-term prognosis that worsens progressively with the number of affected arterial beds. Highlights: Extracardiac vascular disease (CVD/PAD) harbors a negative long-term prognosis in ACS. The risk increases progressively in the long-term with the number of affected beds. CVD and PAD are independent predictors of mortality both in STE-ACS and NSTE-ACS. The combined presence of both CVD and PAD carries the highest risk within each ACS type.